Effect of apical microsurgery on force regulation of incisor teeth during unpredictable force control task. (16th May 2022) - Al‐Manei, Khaled; Almotairy, Nabeel; Al‐Manei, Kholod Khalil; Grigoriadis, Anastasios; Kumar, Abhishek
Abstract: Background: Apical microsurgery (AMS) involves removal of the root‐end which can affect the force regulation of teeth. Objective: To investigate the force regulation of incisor teeth treated with AMS during the unpredictable force control task in comparison with their contralateral teeth with complete root apices, in humans. Methods: Fifteen eligible participants (8 women and 7 men; mean age 52.9 ± SD 4.4 years) performed a standardised unpredictable force control task, which involved pulling and holding a force transducer with AMS‐treated incisors and their contralateral control teeth ( n  = 30 teeth). A series of four load masses: 100, 200, 50 and 300 gm were attached to the force transducer through a string in an unpredictable manner. The obtained force profile was divided into initial and later time‐segments. The peak force and peak force rate during the initial time‐segment, and the holding force and coefficient of variability during the later time‐segments were calculated and compared by the repeated measures analysis of variance. Results: During the initial time‐segment, the peak force and peak force rate were significantly lower in the AMS‐treated teeth than in the controls ( p  = .001, p  = .013, respectively). However, during the later time‐segment, no significant differences in the holding force nor the coefficient of variability were observed between the AMS‐treated teeth and their controls ( p  = .755, p  = .213, respectively). Conclusion: In contrast to incisors with complete normal root apices, AMS‐treated incisors do not show robust changes in force regulation. Abstract : During an unanticipated force control task, incisor teeth treated with apical microsurgery (AMS) demonstrate similar force regulation to natural teeth with complete normal root apices. Aside from the healing of post‐treatment apical periodontitis, AMS treatment plays a crucial role in maintaining tooth function.